2013
DOI: 10.1080/09712119.2012.738224
|View full text |Cite
|
Sign up to set email alerts
|

Acid and alkaline phosphatase activity in broiler chicks fed with different levels of phytase and non-phytate phosphorus

Abstract: Tartrate-resistant acid (ACP) and alkaline phosphatase (ALP) activities were evaluated in the serum and bone of broiler chicks fed with various amounts of non-phytate phosphorus (NPP) or phytase. Data were analysed using a 4)3 factorial design containing four NPP levels per period. Analyses were performed in chicks aged 1Á21 days (0.21; 0.29; 0.37; 0.45 ppm) and 36Á42 days (0.13; 0.21; 0.29; 0.37 ppm) and under three different phytase level treatments (0, 500 and 1000 FTU/kg) for each period. In 42-day-old ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Roberson and Edwards Jr (1994) reported that TAP activity was not influenced by the addition of phytase when used in low Ca levels and high P levels in broiler feeds. These results are supported by the work of Nakagi et al (2013), who concluded that the highest synthesis and expression of this enzyme is observed in P-deficient diets. Additionally, as reported in review, Schmidt et al (2007) suggested that the elevation of enzymes related to bone metabolism is more sensitive in young animals.…”
Section: Discussionsupporting
confidence: 71%
“…Roberson and Edwards Jr (1994) reported that TAP activity was not influenced by the addition of phytase when used in low Ca levels and high P levels in broiler feeds. These results are supported by the work of Nakagi et al (2013), who concluded that the highest synthesis and expression of this enzyme is observed in P-deficient diets. Additionally, as reported in review, Schmidt et al (2007) suggested that the elevation of enzymes related to bone metabolism is more sensitive in young animals.…”
Section: Discussionsupporting
confidence: 71%
“…Similarly, a decrease in dietary Ca from 9.1 to 4.5 g/kg and in total P from 7.2 to 3.7 g/kg linearly decreased dual-energy x-ray absorptiometry-measured total BMD and BMC (Onyango et al, 2003). At day 42, a reduction of dietary avP from 0.37 to 0.13% linearly increased broiler bone tartrate-resistant acid phosphatase concentration (de Souza Nakagi et al, 2013), an indicator of bone resorption activity by osteoclasts (Dacke et al, 1993). Cortical and trabecular bone tissues are actively remodeled throughout the life cycle of broiler chickens (Pratt and Cooper, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…OC had no discernible impact on plasma total protein. According to Nakagi et al (2013), these results highlight the liver's capacity to synthesize these proteins, which also demonstrates the effectiveness of the kidney, immune system, and metabolic processes. These findings are consistent with other research (Al-Shanti and Abo-Omar, 2003;Hajati, 2010) which found no detrimental effects of OC inclusion or enzyme addition on most of the blood's biochemical contents in chickens (Al-Shanti and Abo-Omar, 2003;Hajati, 2010;Sateri et al, 2017).…”
Section: Blood Biochemical Parametersmentioning
confidence: 84%